Applicability of Pap smear and progesterone dosage in artificial insemination in - Paiva, Juliana Hilário Cardoso de; Deboni, Ana Carolina do Nascimento; Marques, Lyvia Freitas; Silva, Laís Siqueira Barboza da; Chapel, Maria Eduarda Masello; Pina, Eliene Porto Sad; Santos, Aline Vieira Pinheiro dos; Almeida, Luis Eduardo Ferreira de; Leite, Dala Kezen Vieira Hardman (Seven Editora, 2024)
Pets have been bred to live with human beings for different reasons, the main one is affective relationships, but also for the purpose of therapy, company for people with special needs, sports, participation in tournaments and exhibitions and reproduction. The pet sector in Brazil is divided into 3 pillars, industry, commerce and animal husbandry services. As a result, animal reproduction and genetic improvement have been gaining ground, due to an increase in the demand for specialists and consequently a significant increase in research in the area. Artificial insemination is the most used biotechnology in this species, especially when natural mating is unfeasible due to anatomical and behavioral issues, in addition to the improvement in genetic gain. In addition, it minimizes the stress caused by handling the animals during conventional mounting and prevents diseases transmitted during copulation. The success of this procedure requires a deep understanding of the reproductive physiology of the species in question. The evaluation of sows and sires involves detailed examinations, including gynecological examination, Pap smear, serum progesterone dosage, and andrological examination. Vaginal cytology aims to identify the phase of the estrous cycle and possible pathologies through cells of its epithelium, while serum progesterone measurement aims to have a greater accuracy of the moment of insemination and the andrological examination aims to evaluate the fertility of the sire. In the general clinical evaluation, several parameters are considered, such as reproductive and pathological history, vaccination and parasitic protocols. Pap smear is considered a more practical, lower-cost and easier to apply method, reflecting changes in estrogen concentration and not progesterone. The hormonal dosage of progesterone is performed at the end of proestrus or the beginning of estrus, which is when it precedes the LH peak. Upon reaching peak LH, progesterone levels increase. This means that there will be ovulation, which is the ideal time to perform intravaginal artificial insemination. DOI:https://doi.org/10.56238/sevened2024.007-081